Sesamin modulation of lipid class and fatty acid profile in early juvenile teleost, Lates calcarifer, fed different dietary oils - Alhazzaa, Ramez; Bridle, A.; Carter, C.; Nichols, P. (2012)
Sesamin, a major sesame seed lignan, has diverse biological functions including the modulation of molecular actions in lipid metabolic pathways and reducing cholesterol levels. Vertebrates have different capacities to biosynthesize long-chain PUFA from dietary precursors and sesamin can enhance the biosynthesis of ALA to EPA and DHA in marine teleost. Early juvenile barramundi, Lates calcarifer, were fed for two weeks on diets rich in ALA or SDA derived from linseed or Echium plantagineum, respectively. Both diets contained phytosterols and less cholesterol compared with a standard fish oil-based diet. The growth rates were reduced in the animals receiving sesamin regardless of the dietary oil. However, the relative levels of n-3 LC-PUFA in total lipid, but not the phospholipid, increased in the whole body by up to 25% in animals fed on sesamin with ALA or SDA. Sesamin reduced the relative levels of triacylglycerols and increased polar lipid, and did not affect the relative composition of phospholipid subclasses or sterols. Sesamin is a potent modulator for LC-PUFA biosynthesis in animals, but probably will have more effective impact at advanced ages. By modulating certain lipid metabolic pathways, sesamin has probably disrupted the body growth and development of organs and tissues in early juvenile barramundi. © 2012 Elsevier Ltd. All rights reserved.